2017
DOI: 10.1002/wps.20385
|View full text |Cite
|
Sign up to set email alerts
|

The current conceptualization of negative symptoms in schizophrenia

Abstract: Negative symptoms have long been conceptualized as a core aspect of schizophrenia. They play a key role in the functional outcome of the disorder, and their management represents a significant unmet need. Improvements in definition, characterization, assessment instruments and experimental models are needed in order to foster research aimed at developing effective interventions. A consensus has recently been reached on the following aspects: a) five constructs should be considered as negative symptoms, i.e. bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
312
2
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(343 citation statements)
references
References 173 publications
(202 reference statements)
11
312
2
18
Order By: Relevance
“…In line with this, Slotema et al () reported that the mean age of AVH onset was 16 years in adults with BPD, compared with 20 years in adults with SZ. Fifth, the PANSS has been criticized for not comprehensively covering all relevant negative symptom dimensions (ie, blunted affect, alogia, anhedonia, asociality and avolition) (Marder & Galderisi, ). Finally, this is a cross‐sectional study.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, Slotema et al () reported that the mean age of AVH onset was 16 years in adults with BPD, compared with 20 years in adults with SZ. Fifth, the PANSS has been criticized for not comprehensively covering all relevant negative symptom dimensions (ie, blunted affect, alogia, anhedonia, asociality and avolition) (Marder & Galderisi, ). Finally, this is a cross‐sectional study.…”
Section: Discussionmentioning
confidence: 99%
“…Based on factor analysis studies, they can be divided into deficits of expression and motivation/pleasure (Lyne, Renwick, Grant, et al, ), and recently developed scales have reflected this negative symptom structure (Barch, ; Strauss et al, ). Deficits of expression include affective flattening and alogia, whereas motivation/pleasure domain symptoms include avolition, anhedonia and asociality (Marder & Galderisi, ). Some studies have suggested different correlates for each domain and domain‐based research is ongoing (Strauss et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…SZ is also a heterogeneous disorder, marked by the variable presentation of positive symptoms (ie, hallucinations and delusions), negative symptoms (ie, amotivation and diminished expression), and cognitive deficits. Historically, the core negative symptoms consisted of anhedonia, asociality, alogia, avolition, and affective flattening . However, the current conceptualization of negative symptoms outlines two separate but interrelated subdomains: amotivation (within which anhedonia is subsumed) and diminished expression (including alogia and affective flattening) .…”
Section: The Presentation Of Anhedonia In Mdd and Szmentioning
confidence: 99%
“…Patients with MDD are unable to adequately utilize rewarding or positive feedback to optimize reward outcomes; however, they do not differ from controls in their ability to utilize punishment information to avoid loss . Further, patients with SZ often experience memory deficits which may impede normal reward learning and pleasure recall, contributing to inaccurate appraisals of rewards and impaired decision‐making in pursuit of such rewards …”
Section: The Presentation Of Anhedonia In Mdd and Szmentioning
confidence: 99%